POLA STRATEGI PROMOSI DALAM PROSES PEMASARAN GERABAH KASONGAN: STUDI KASUS UMKM SENTRA INDUSTRI KERAMIK DI KASONGAN, KABUPATEN BANTUL, D.I. JOGJAKARTA - Syamsuri, Syamsuri (Jurnal Ilmiah Pena: Sains dan Ilmu Pendidikan, 2018)
The tight competition between Indonesia and other developed countries in mastering the market share both within and outside the country resulted in MSMEs should think hard to determine the pattern of marketing strategy and provide good product quality. Kasongan Pottery Industrial Center has penetrated its product market to Asian and European countries, then the need for the right promotional strategy to remain in demand abroad. Based on the findings, the pattern of Gerabah marketing strategy still needs to be improved because there is a tendency of knowledge shortage and awareness of craftsmen about the importance of promotion and lack of funding in promoting promotion. Then there is the need for awareness of knowledge improvement through Training and participation of commitments with the government and related agencies in promoting marketing.Â Key Word: Promotion Strategy, Marketing of MSMEs Products